Multimodality approach to mediastinal staging in non-small cell lung cancer. Faults and benefits of PET-CT: a randomised trial. Issue 4 (17th December 2010) - Fischer, Barbara M; Mortensen, Jann; Hansen, Hanne; Vilmann, Peter; Larsen, Søren S; Loft, Annika; Bertelsen, Anne K; Ravn, Jesper; Clementsen, Paul; Høegholm, Asbjørn; Larsen, Klaus R; Dirksen, Asger; et al.
Abstract : Background: Correct mediastinal staging is a cornerstone in the treatment of patients with non-small cell lung cancer. A large range of methods is available for this purpose, making the process of adequate staging complex. The objective of this study was to describe faults and benefits of positron emission tomography (PET)-CT in multimodality mediastinal staging. Methods: A randomised clinical trial was conducted including patients with a verified diagnosis of non-small cell lung cancer, who were considered operable. Patients were assigned to staging with PET-CT (PET-CT group) followed by invasive staging (mediastinoscopy and/or endoscopic ultrasound with fine needle aspiration (EUS-FNA)) or invasive staging without prior PET-CT (conventional work up (CWU) group). Mediastinal involvement (dichotomising N stage into N0–1 versus N2–3) was described according to CT, PET-CT, mediastinoscopy, EUS-FNA and consensus (based on all available information), and compared with the final N stage as verified by thoracotomy or a conclusive invasive diagnostic procedure. Results: A total of 189 patients were recruited, 98 in the PET-CT group and 91 in the CWU group. In an intention-to-treat analysis the overall accuracy of the consensus N stage was not significantly higher in the PET-CT group than in the CWU group (90% (95% confidence interval 82% to 95%) vs 85% (95% CI 77% to 91%)). Excluding the patients in whom PET-CT was not performed (n=14) the difference was significant (95% (95% CI 88% to 98%) vs 85% (95% CI 77% to 91%), p=0.034). This was mainly based on a higher sensitivity of the staging approach including PET-CT. Conclusion: An approach to lung cancer staging with PET-CT improves discrimination between N0–1 and N2–3. In those without enlarged lymph nodes and a PET-negative mediastinum the patient may proceed directly to surgery. However, enlarged lymph nodes on CT needs confirmation independent of PET findings and a positive finding on PET-CT needs confirmation before a decision on surgery is made. Clinical trial number: NCT00867412.